Application of the Teaching Factory Model to the Learning Outcomes of Class XI Students in the Heavy Equipment Engineering Department - M Giatman; Nurhasan Syah; Iffarial Nanda; Wagino Wagino (Universitas Negeri Padang, 2022)
The dream of a 'link and match' between schools and industry to become a reality is a big target to be achieved by the government. For that we need the support of superior human resources (HR) so that development can run well. One of the concepts of the learning approach carried out by the Ministry of Education and Culture is for schools to produce superior human resources in accordance with the needs of the industrial world through the teaching factory (TEFA) program. Recent research has demonstrated an urgent need for future engineers. This research is a continuous experimental study for 2 semesters by applying it to all samples, to see if there is a significant effect on TEFA. Research that uses the Ex-Post Facto approach. The population in this study were students of the Heavy Equipment Engineering Department at SMK Negeri 1 Guguak. The sample is class XI students of the Heavy Equipment Engineering Department who have obtained the Teaching Factory Learning Model as many as 32 people who were selected using a non-probability technique, namely Purposive Sampling. The data analysis technique used is descriptive analysis. The result of t-test is smaller than t-table (-0.381 < 1.697). This shows that the negative effect of the application of (TEFA) on the Learning Outcomes of Class XI Students in Powertrain and Undercarriage subjects is not only insignificant or very small, it can even be said to have no effect.